Hepatitis C Knowledge and Recent Diagnosis Affect Hepatitis C Treatment Willingness in Persons Living With HIV. (1st May 2021) - Cachay, Edward R.; Torriani, Francesca J.; Hill, Lucas; Rajagopal, Amutha; Yin, Jeffrey; Bamford, Laura; Mathews, William C.
Abstract : Background: We assessed the impact of health literacy and hepatitis C (HCV) knowledge on HCV treatment willingness among people living with HIV (PLWH) at an academic HIV clinic. Methods: Cross-sectional analysis of PLWH coinfected with HCV who completed health literacy, HIV literacy, and HCV knowledge inventories. We estimated the prevalence of low health literacy, HIV knowledge, and HCV knowledge sampled from 3-comparison groups: PLWH not referred for HCV, referred but who "not showed" to the HCV clinic, and referred and attended the HCV clinic. We used mixed-model linear and logistic regression to ascertain predictors of low health literacy, HIV knowledge, HCV knowledge, and predictors of willingness to start HCV treatment. Results: We enrolled 151 PLWH; 17% were female, 38% non-White, and 60% without a high-school education. Approximately, 68% were men who have sex with men, of whom 62% used intravenous drugs. The prevalence of low health, HIV knowledge, and HCV knowledge was 10%, 32%, and 29%, respectively. Predictors of low health literacy were being Hispanic, cirrhotic, and not completing high-school education. Low HCV knowledge was observed in female, non-White, and those diagnosed with HCV for a decade. In adjusted analyses, PLWH living with HCV for a decade (OR: 0.23) were less likely to be very willing to be treated for HCV. By contrast, those with high HCV knowledge were more likely to be very willing to receive treatment (OR: 1.27). Conclusion: Low HCV knowledge and living with HCV for at least a decade are under-recognized negative predictors for PLWH's willingness to receive HCV treatment. Clinical Trials Registration: ClinicaTrials.gov identifier: NCT20170991. Abstract : Supplemental Digital Content is Available in the Text.